2006
DOI: 10.1142/s0218202506001790
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Flows of Thermal Viscous Incompressible Fluids With Convective-Radiation Effects

Abstract: The work deals with the coupled system constituted by the equations of motion and energy with nonlinear and nonlocal boundary conditions in order to describe the thermal flow motion of a class of non-Newtonian fluids and the convective-radiation balance, respectively. For the constitutive laws in an n-dimensional space (n = 2, 3), the stress tensor and the heat flux are considered related with the (p, q) coercivity parameters for p > 2n/(n + 1) and q > np/(p(n + 1) − n), respectively. The radiation character o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In particular, the same property holds by replacing ∇ by D. The above considerations, together with the nonnegativity of the integrands that appear on the left-hand side of inequality (5.11), allow us to pass to the limit by using Fatou's lemma. This yields 12) for each k = 3. Hence,…”
Section: By Taking the Difference Between Equations (52) And (53) mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the same property holds by replacing ∇ by D. The above considerations, together with the nonnegativity of the integrands that appear on the left-hand side of inequality (5.11), allow us to pass to the limit by using Fatou's lemma. This yields 12) for each k = 3. Hence,…”
Section: By Taking the Difference Between Equations (52) And (53) mentioning
confidence: 99%
“…Without any claim of completeness, in addition to the articles already quoted, we would like to mention the following articles related to the problems treated in this paper: [1], [4], [9], [10], [11], [12], [14], [15], [24], [28], [29], [30], [31], [36], [37], [38], [39], and all the relevant references therein.…”
mentioning
confidence: 99%
“…In [10], the particular case of Navier-Stokes-Fourier problem includes the radiation behavior at the two-dimensional space. In [12], the Joule effect is neglected and Dirichlet boundary condition for the fluid velocity is taken into account, since we deal with the existence of a weak solution capturing the radiation behavior in the three-dimensional space and the shear thinning phenomenon exhibited by a broader class of non-Newtonian fluids. That is, we provide upper bounds to the exponent of the nonlinear convective-radiative term and lower bounds to the exponent relative to the principal nonlinear elliptic operator than the classical restriction, p > 3n/(n + 2), due to the existence of the convective term.…”
Section: Definitionmentioning
confidence: 99%
“…In the article [46] the problem (1.1) is studied provided p = n = 2 by the method of straightening the boundary. In [15][16][17][18][19] very interesting, physical meaningful, problems are deeply studied. In [34] it has been shown that the unique weak solution u of (1.4) with (1.2) satisfies u ∈ L ∞ (I, W 2,2+ (Ω)) provided p ∈ [2, 4) and n = 2.…”
Section: Introductionmentioning
confidence: 99%